Collective Beliefs on Responsible Investment. (March 2016) - Dumas, Christel; Louche, Céline
The financial community does not seem to have shifted to greater sustainability, despite increasing awareness and concerns around social and environmental issues. This article provides insights to help understand why. Building on responsible investment (RI) data from the U.K. financial press between 1982 and 2010, the authors examine the collective beliefs which financial actors rely on to take decisions under uncertainty, as a way of understanding the status of and implications for RI mainstreaming. The analysis of collective beliefs through five periods of RI leads us to define two theoretical dimensions—justifying RI and practicing RI—that characterize how mainstream actors collectively make sense of RI. The authors' analysis reveals that the RI collective beliefs currently (a) do not provide a favorable environment for RI mainstreaming and (b) need to be taken into account when discussing the value of sustainability.